CONSENTS OF POSSESORS OF ADJACENT TERRITORIES WHEN CONSTRUCTING STRUCTURES CLOSE TO THE COMMON BOUNDARY OF A LAND LOT - Gaudėšius, Rimvydas (Teisė, 2017)
The legislation, scientific articles and specific practical situations are analyzed in the article. Generalizing the information and data collected, the most frequent issues are revealed and the proposals to amend specific provisions of the legislation are therefore presented. The research performed showed that even 70 percent of all applications regarding construction works close to the boundary of a land lotare not upheld.